IbM PELATIHAN PEMBUATAN MEDIA PEMBELAHARAN INTERAKTIF BERBASIS ICT BAGI GURU SDN DALANGAN 02 DAN 03 TAWANGSARI - Sari, Nurratri Kurnia; Purbosari, Para Mitta; Prasetyo, Koko; Angganing, Paradika (Jurnal Terapan Abdimas, 2021)
Abstract. Dalangan Elementary School 02 and 30 Tawangsari, Sukoharjo District, Sukoharjo Regency are located in the village of Dalangan, which is an in-depth area. School facilities such as LCDs, notebooks and even the internet already exist in several schools in the Merauke Cluster Elementary Schools in Nguter District, Sukoharjo Regency. The fact is that teachers are still few in using ICT media as a medium of learning, teachers in these schools still mostly use image media and conventional media. Whereas in every school, LCD and notebook are available. However, only a few teachers have not yet mastered the technology of making ICT-based media. The use of ICT media uses more exposure to power pints. The use of power points that is displayed is less interactive and tends to be exposive. So that the use of ICT media is not optimal. Based on these problems, the formulation of the problem to be answered is "Can training be able to provide knowledge about the making of interactive learning media through power point animation and Flash for the RA Kartini KKG Group in Sukoharjo District, Sukoharjo Regency? The results achieved through this activity are as follows; 1) There is increased skills in designing and converting offline RPP to online. 2) There is an increase in the knowledge and skills of the teachers about the making of video presentation learning media through OBS studio and online evaluation Quiziz. 3) Availability of online lesson plans, presentation video learning media through OBS studio and online evaluation Quiziz. 4) The involvement of partner teachers in community service activities, 100% starting from socialization, counseling, training and assistance in making ICT-based interactive learning media. 5) Activity reaches 80% of partner participants who are actively participating in the training must be able to do in developing and making ICT-based interactive learning media Abstrak.Sekolah Dasar Negeri Dalangan 02 dan 30 Tawangsari kecamatan Sukoharjo Kabupaten Sukoharjo terletak di desa Dalangan yang termasuk daerah pendalaman. Fasilitas sekolah seperti LCD, notebook bahkan internet sudah ada di beberapa sekolah Gugus Merauke Sekolah Dasar seKecamatan Nguter Kabupaten Sukoharjo. Kenyataan guru masih sedikit dalam menggunakan mediia ICT sebagai media pembelajaran, guru di sekolah tersebut lebih banyak masih menggunakan media gambar dan media konvensional. Padahal di setiap sekolah sudah tersedia LCD dan notebook. Akan tetapi hanya beberapa guru yang belum bisa menguasai teknologi pembuatan media berbasis ICT. Penggunaan media ICT, lebih banyak menggunakan pemaparan pada power pint. Penggunaan power point yang ditampilkan masih kurang interaktif dan cenderung pemaparan. Sehingga penggunakan media ICT belum maksimal. Berdasarkan permasalahan tersebut, rumusan masalah yang akan dijawabadalah “Apakah dengan pelatihan mampu memberikan pengetahuan tentang pembuatan media pembelajaran interaktif melalui animasi power point dan Flash bagi KKG Gugus RA Kartini seKecamatan Sukoharjo Kabupaten Sukoharjo? Hasil yang dicapai melalui kegiatan ini adalah sebagai berikut; 1)Adanya peningkatan ketrampilan dalam merancang dan merubah RPP luring ke daring. 2)Adanya peningkatan pengetahuan dan keterampilan para guru tentang pembuatan media pembelajaran video presentasi melalui OBS studio dan evaluasi online Quiziz. 3)Tersedianya RPP daring, media pembelajaran video presentasi melalui OBS studio dan evaluasi online Quiziz. 4)Keterlibatan guru mitra dalam kegiatan pengabdian masyarakat, 100% mulai dari kegiatan sosialisasi, penyuluhan, pelatihan dan pendampingan pembuatan media pembelajaran interaktif berbasis ICT. 5)Kaeaktifan mencapai 80% peserta mitra yang secara aktif mengikuti pelatihan harus mampu melakukan dalam  mengembangkan dan membuat media pembelajaran interaktif berbasis ICT.